PERANCANGAN SISTEM E-COMMERCE BERBASIS WEB PADA TOKO INDAH SURYA FURNITURE - Nana Saharna; Kasman Rukun (Universitas Negeri Padang, 2019)
Indah Surya Furniture Shop still uses simple media in carrying out its business activities. Product promotion still uses brochures, banners and radios. While the product ordering process still uses WhatsApp and telephone, and for the sales report it is still made manually so that simply the media used indicates that the sales results have not been optimized. In order to increase sales results the system should be able to promote products easily and can order products quickly. Therefor, a web-based e-commerce system is used to help owners promote and market their products. The presence of an e-commerce system is expected to help owners market their products, and can help consumers buy products according to their needs. The design of the e-commerce system uses UML modeling (Unified Modeling Language) by using object-oriented visualization diagrams. The programming language used is the PHP (PHP Hypertext Preprocessor) programming language based on CodeIgniter and Javascript, with MySQL as the Database Management System (DBMS) and Sublime Text 2 as editors. The resulting web-based e-commerce system can market products in a wider area and can provide information about products quickly, and with this e-commerce system consumers will be easier to order products. Keywords: E-commerce system, Web, Codeigniter.